The Effect of Self Efficacy and Workload on Work Stress of Public Elementary School Teachers in Bekasi - Ifnuari, Reza (Universitas Negeri Jakarta, 2025)
Background Work stress is one of the main challenges faced by teachers in carrying out their professional duties, especially in the elementary school environment which has high dynamics. Factors such as heavy workload and low levels of self-efficacy are believed to contribute to increased psychological stress in carrying out the role of educator. Purpose This study was conducted to find out the extent of the level of work stress of classroom teachers in public elementary schools spread throughout the North Bekasi District, Bekasi City. This study also aims to examine the influence of self-efficacy and workload on work stress, as well as the relationship between self-efficacy and the workload itself. Method This study involved 172 elementary school teachers in the North Bekasi District area. The instrument used was a survey, and the data was analyzed using the path analysis method. This method was chosen because it is able to simplify the process of analyzing the causal relationship between the variables studied. Result The results showed that: 1) There was a significant influence between self-efficacy on work stress, 2) There was a significant influence between workload on work stress, and 3) There was an influence between self-efficacy on workload. Value This research makes an important contribution to the understanding of the factors that affect teachers' work stress. These findings can be used as a basis for designing interventions aimed at improving self-efficacy and workload management, in order to reduce teachers' work stress and support their well-being in the primary education environment.